China Population and Development Studies - Zheng, Zhenzhen; Liu, Hongyan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
This journal provides an international platform for discussions on topics related to various population phenomena and development issues, complemented by a strong representation of the research trend and achievement in China and other Asian countries. The journal, hosted by China Population and Development Research Center, draws on the energetic and resourceful Chinese research community as well as in close contact with the Asian research community in the area, features the Asian perspective on the field of population studies. This journal publishes original research papers including empirical studies, theoretical and methodological analysis, policy reviews, and survey reports in population and development related fields. Interdisciplinary perspectives are also encouraged to help improving understandings of demographic dynamics as well as refining research methods. Relevant topic areas include but are not limited to: Demography and population studies Population policy and planning Population and health International and internal migration Ageing and population dynamics Fertility, fertility preference, sex ratio at birth Population Economics Comparative population studies Modeling and projection Social science methods and methodology Population Sociology.
Keywords: Health promotion; Population; Demography; Demography; Health Promotion and Disease Prevention; Social/Human Development Studies; Population Economics